THE ROLE OF VARIATIVE APPROACHES IN DEVELOPING STUDENTS' INDEPENDENCE IN LEARNING ACTIVITIES - Husniddin Tojiev (The Conference Hub, 2025)
This article analyzes the role of variational approaches in developing students' independence in their learning activities. Variational approaches provide students with a variety of teaching methods, allowing them to independently master their own knowledge. Such approaches increase students' creative thinking, problem-solving skills, and make the learning process more effective. The article reveals the importance of variational approaches in developing students' independent learning activities.
Keywords: education, variability, methodology, effectiveness, educational process, innovative methods, pedagogical views.